(untitled) (MUZIKOLOGIJA-MUSICOLOGY, 2023)
Igor Stravinsky’s late style is usually considered in terms of the works’ structure. Following Joseph N. Straus, this article attempts to highlight expressive, semantic and self-referential dimensions in Stravinsky’s late compositions. These dimensions emerge there with particular clarity and partly contradict the usual assessments of this music as abstract and constructivist; as such, they also challenge the composer’s own statements.